Teachers' Readiness to Implement the Deep Learning Approach in Merdeka Curriculum: An Analysis Based on Psychopedagogical Characteristics - Eka Budhi Santosa; Fatma Sukmawati; Jovita Ridhani; Sari Trisnaningsih; Relly Prihatin (JTP - Jurnal Teknologi Pendidikan, 2025)
This study aims to analyze the readiness of vocational high school (SMK) teachers to implement the deep learning approach within the Merdeka Curriculum, based on psychopedagogical characteristics, particularly self-efficacy and perceptions of the learning environment. Employing a quantitative correlational approach, data were collected through a closed-ended questionnaire administered to 285 teachers across three administrative regions in Central Java: Boyolali, Klaten, and Salatiga. The results reveal a significant positive correlation between self-efficacy and teacher readiness (r = 0.319; p < 0.01), as well as between the learning environment and teacher readiness (r = 0.381; p < 0.01). These findings highlight the critical role of teachers’ confidence in using technology and the supportive digital learning environment in facilitating the successful adoption of deep learning pedagogy. Therefore, enhancing individual teacher capacity and fostering a conducive learning environment are key strategies to support effective pedagogical transformation in the era of the Merdeka Curriculum.